THE ROLE AND IMPORTANCE OF POPULATION-RESETTLEMENT PROCESS FOR THE DEVELOPMENT OF KHARKIV REGION SOCIO-NATURAL SYSTEMS - Нємець, Костянтин; Кравченко, Катерина (Human Geography Journal, 2016)
In the article the author gave the definition population-resettlement processes, conducted structural analysis of settlement of the Kharkiv region, describes the main types of settlement structures defined their characteristics. In the article found the framework of urban settlement in the Kharkiv region. Factors of formation and development population network Kharkiv, modern features of its development. Found three waves of migration in the Kharkiv region. The article contains the analysis of the process of formation of communities in Kharkiv region and determined their types.